Analisis Yuridis Perlindungan Hukum Terhadap Tenaga Kerja Indonesia Ditinjau Dari Undang-Undang Nomor 18 Tahun 2017 Tentang Perlindungan Pekerja Migran Indonesia - Musrin, Musrin; Simatupang, Bachtiar; Anatami, Darwis (Jurnal Syntax Fusion, 2022)
Indonesian Migrant Workers (TKI) is one of the country's largest foreign exchange. Along with the number of TKI who work abroad, the increasing treatment that is not in accordance with what is expected by the workers. The treatment of employers or employers is often contrary to applicable law. The provisions in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers Abroad regulates how the protection of Indonesian Migrant Workers working abroad, labor law or employment (Labor Law) is part of the law regarding the regulation of labor relations, both individual and collective. Research is a basic tool in the development of science and technology. This is because research aims to reveal the truth in a systematic, methodological, and consistent manner. The data and information that the author uses in writing this thesis are obtained or obtained through normative research.Research is a basic tool in the development of science and technology. This is because research aims to reveal the truth in a systematic, methodological, and consistent manner. The data and information that the author uses in writing this thesis are obtained or obtained through normative research. The 1945 Constitution of the Republic of Indonesia Article 27 paragraph (2) states that every Indonesian citizen has the right to work and a decent living for humanity. In fact, limited job opportunities in the country have caused many Indonesian citizens to seek work abroad. Juridically the laws and regulations in the field of placement and protection of Indonesian Migrant Workers (TKI) are not synchronized vertically or horizontally. While sociologically the level of legal awareness of prospective Indonesian Migrant Workers (TKI), lack of supervision from labor inspectors, weak law enforcement. Legal Protection for Indonesian Migrant Workers Working Abroad as regulated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers Abroad. It must start with reforming the law. It aims to protect Indonesian Migrant Workers (TKI) who work abroad properly